Transient Nascent Adhesion at the Initial Stage of Cell Adhesion Visualized on a Plasmonic Metasurface. Issue 1 (29th November 2021) - Lee, Shi Ting; Kuboki, Thasaneeya; Kidoaki, Satoru; Aida, Yukiko; Ryuzaki, Sou; Okamoto, Koichi; Arima, Yusuke; Tamada, Kaoru
Abstract : A plasmonic metasurface composed of self‐assembled gold nanoparticles enables high‐speed interfacial imaging with high axial and lateral resolution down to the theoretical limit under a widefield microscope. This high‐spatiotemporal resolution imaging method monitors "early molecular events" in the adhesion of 3T3 fibroblasts expressing Venus‐paxillin and LifeAct‐mScarlet, revealing unique transient cell dynamics. Upon attaching to the SiO2 ‐coated plasmonic metasurface, cells exhibit fibrous nascent adhesions spreading radially at the periphery, together with actively moving membrane blebs. These fibrous nascent structures exist transiently during passive spreading and disappear upon transition to active spreading with mature focal adhesions (FAs). The structure forms on a poor‐cell‐adhesive SiO2 ‐coated surface but not on a fibronectin‐preadsorbed cell‐adhesive surface, suggesting that it temporarily anchors cells to the interface but maintains freedom before active cell spreading. These momentary molecular‐level phenomena at the nanointerface are successfully captured by the herein described high‐spatiotemporal resolution live‐cell imaging method using a plasmonic metasurface. Abstract : Fine fibrous nascent adhesions spreading radially at the cell contact position are observed on a poor‐cell‐adhesive SiO2 ‐coated surface at the early stage of cell adhesion. These momentary molecular‐level phenomena at the nanointerface are successfully captured by our high‐spatiotemporal resolution live‐cell imaging method using a plasmonic metasurface composed of self‐assembled gold nanoparticles.